The Prevalence of Staphylococcus aureus in the Oral Cavity of Healthy Adults in Malaysia - Amir Harriz Azmi; Normaliza Ab Malik; Siti Noor Adnalizawati Adnan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by Scopus